Tingkat Stres dan Pola Konsumsi terhadap Kejadian Hipertensi pada Pasien Dewasa: Studi Cross-Sectional - Belinda Widya Renda; Sri Sumarmi (Media Gizi Kesmas, 2023)
Background: In Indonesia, hypertension is a very common disease. High and chronic stress levels can contribute to the risk of developing hypertension. Uncontrolled consumption patterns with excessive fat and salt content but very little fiber consumption can increase the risk of developing hypertension. Objectives: To determine the association of stress level and consumption pattern with hypertension in adult patients. Methods: This study is a quantitative research. This study used a cross-sectional design, which was conducted on 365 adult patients, the sample was taken by accidental sampling. Statistical analysis using chi-square test and correlation contingency test. This study was conducted on a population of adult patients at the Sukodono Health Center, Sukodono District, Sidoarjo Regency. The research instrument used the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) for consumption patterns and the Depression Anxiety Stress Scale (DASS-21) for stress levels. Results: The results showed that there was no significant relationship between stress level and hypertension (p=0.143; r=0.361) and there was a significant relationship between consumption pattern and hypertension. Conclusions: Stress level is not the main factor causing hypertension in patients. Consumption patterns can be one of the factors causing hypertension in patients.